Studies in Baroque: Festschrift Ton Koopman - Clement, Albert 1962-; Koopman, Ton 1944- (Bonn Butz, 2014)
Ton Koopman is one of the world's best known and most recognised experts, particularly in baroque and classical music. The friendly conductor, organist and harpsichord player is celebrating his 70th birthday on 2nd October, and his colleagues and friends decided to mark this by publishing a veritable and compendious Festschrift.Inevitably, the focus of the total of 19 essays (including a discography and bibliography), which have been written by leading international academics and practitioners, is on Bach and the organ/organ music, but they also touch on the fine arts and theology.
Keywords: 17th Century (1601-1700); 18th Century (1701-1800); Music history; Baroque